INDEKS VEGETASI DARI CITRA SATELIT ALOS UNTUK MEMPERKIRAKAN CADANGAN KARBON ATAS PERMUKAAN DI HUTAN MANGROVE - Suyadi Suyadi; Y.I. Ulumudin; R Vebriansyah (BERITA BIOLOGI, 2013)
Mangrove forests sequestrate and store a lot of carbon and are important to tackle climate change. However, much of these forests have been cleared dramatically and such clearings destroyed carbon sinks and released carbon into the atmosphere as carbon dioxide. The international climate agreements highlight Reduced Emissions from Deforestation and Forest Degradation (REDD+) as a key and effective option for mitigating climate change. To help making REDD+ a reality, an alternative approach is needed to measure above ground carbon stock quickly and accurately. Here, we link ground-based data collected from field measurement using belt transect method with satellite image data of the ALOS AVNIR-2. The objectives are to identify the characteristics of mangrove vegetation, to estimate the amount of above ground carbon stock, and to examine capability of vegetation indices of NDVI, SR, dan SAVI from the ALOS AVNIR-2 to estimate the amount of above ground carbon stock in mangrove. Results showed that the mangrove vegetation in Gugus Pulau Pari was relatively diverse and this forest contained above ground carbon between 4694.35 and 42841.25 kg/m2. The statistics analyses showed that there was no significant correlation between the vegetation indices of NDVI, SR, and SAVI with the amount of above ground carbon stock in tropical mangrove forest. In short, the vegetation indices of NDVI, SR, and SAVI from the ALOS AVNIR-2 were not sufficient to estimate the amount of above ground carbon stock in tropical mangrove forest.